FLEXIBLE EDUCATION: THE WAY FORWARD IN HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 16 August 2016 – Flexibility in education that allows for the local education system to be redesigned in line with the current technological changes can be seen as among those that would shape the future of higher education in the country.